Dynamic and unique nucleolar microenvironment revealed by fluorescence correlation spectroscopy. Issue 3 (17th November 2014) - Park, Hweon; Han, Sung‐Sik; Sako, Yasushi; Pack, Chan‐Gi
Abstract : Organization and functions of the nucleolus is maintained by mobilities and interactions of nucleolar factors. Because the nucleolus is a densely packed structure, molecular crowding effects determined by the molecular concentrations and mobilities in the nucleolus should also be important for regulating nucleolar organization and functions. However, such molecular property of nucleolar organization is not fully understood. To understand the biophysical property of nucleolar organization, the diffusional behaviors of inert green fluorescent protein (GFP) oligomers with or without nuclear localization signals (NLSs) were analyzed under various conditions by fluorescence correlation spectroscopy. Our result demonstrates that the mobility of GFPs inside the nucleolus and the nucleoplasm can be represented by single free diffusion under normal conditions, even though the mobility in the nucleolus is considerably slower than that in the chromatin region. Moreover, the free diffusion of GFPs is found to be significantly size‐ and NLS‐dependent only in the nucleolus. Interestingly, the mobility in the nucleolus is highly sensitive to ATP depletion, as well as actinomycin D (ActD) treatment. In contrast, the ultra‐structure of the nucleolus was not significantly changed by ATP depletion but was changed by ActD treatment. These results suggest that the nucleolus behaves similarly to an open aqueous‐phase medium with an increased molecular crowding effect that depends on both energy and transcription.—Park, H., Han, S.‐S., Sako, Y., Pack, C.‐G. Dynamic and unique nucleolar microenvironment revealed by fluorescence correlation spectroscopy. FASEB J. 29, 837–848 (2015). www.fasebj.org